SOSIALISASI POLITIK DAN PENDIDIKAN POLITIK MELALUI PLAFORM INSTAGRAM (STUDI PADA AKUN @PINTERPOLITIK) - togar, togar; Zalpa, Yulion; Juainah, Norma (Jurnal Studi Ilmu Politik, 2024)
The means of political socialization and political education are family, school, social groups, work, mass media and political contacts. This research will focus on the means of political socialization and political education through mass media, namely the Instagram platform @Pinterpolitik. The aim of this research is to determine the forms and patterns of political socialization and political education on the Instagram account @pinterpolitik. This type of research is descriptive qualitative. This research found that people must understand the capabilities of their own country and must believe that their country has advantages. They must also have a critical attitude to be able to determine their attitude towards political events that occur, and they must also understand the rules, laws and regulations.